2015
DOI: 10.1021/acs.jafc.5b01307
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Neutrophil Responses by the Essential Oil of Artemisia kotuchovii and Its Constituents

Abstract: Essential oils were obtained by hydrodistillation of the flowers+leaves and stems of Artemisia kotuchovii Kupr. (AKEOf+l and AKEOstm, respectively) and analyzed by gas chromatography (GC) and gas chromatography-mass spectrometry (GC/MS). The primary components of the oils were estragole, (E)- and (Z)-β-ocimenes, methyl eugenol, limonene, spathulenol, β-pinene, myrcene, and (E)-methyl cinnamate. Seventy four constituents were present at concentrations from 0.1 to 1.0%, and 34 compounds were identified in trace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(78 citation statements)
references
References 50 publications
(129 reference statements)
4
71
2
1
Order By: Relevance
“…Essential oil was obtained by hydrodistillation using a Clevenger type apparatus, as described previously 9 . For the hydrodistillation, we used conditions accepted by the European Pharmacopoeia (European Directorate for the Quality of Medicines, Council of Europe, Strasbourg, France, 2014) to avoid artifacts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential oil was obtained by hydrodistillation using a Clevenger type apparatus, as described previously 9 . For the hydrodistillation, we used conditions accepted by the European Pharmacopoeia (European Directorate for the Quality of Medicines, Council of Europe, Strasbourg, France, 2014) to avoid artifacts.…”
Section: Methodsmentioning
confidence: 99%
“…GC-MS analysis was performed with an Agilent 5975 GC-MSD system (Agilent Technologies, Santa Clara, CA, USA), as reported previously 9 . An Agilent Innowax FSC column (60 m × 0.25 mm, 0.25 µm film thickness) was used with He as the carrier gas (0.8 mL/min).…”
Section: Methodsmentioning
confidence: 99%
“…Lawsochylin A (Table 1) and (4 S )-4-hydroxy-α-tetralone isolated from Lawsonia inermis also inhibited f MLF-induced responses [73]. Recently, we found that 6-methyl-3,5-heptadien-2-one, which is a minor constituent in essential oils from Artemisia kotuchovii [196] and oleoresins from paprika and tomato [197], could non-specifically inhibit all functional responses that we tested in human neutrophils and FPR1-transfected HL-60 cells, including f MLF-stimulated Ca 2+ flux and chemotaxis, PMA-induced ROS production, and interleukin 8-induced Ca 2+ flux. We concluded that this compound may interfere with intracellular signaling pathways common to both FPR1 and CXCR1/2 [196].…”
Section: Small-molecule Non-peptide Fpr1 Antagonists and Their Synmentioning
confidence: 99%
“…Recently, we found that 6-methyl-3,5-heptadien-2-one, which is a minor constituent in essential oils from Artemisia kotuchovii [196] and oleoresins from paprika and tomato [197], could non-specifically inhibit all functional responses that we tested in human neutrophils and FPR1-transfected HL-60 cells, including f MLF-stimulated Ca 2+ flux and chemotaxis, PMA-induced ROS production, and interleukin 8-induced Ca 2+ flux. We concluded that this compound may interfere with intracellular signaling pathways common to both FPR1 and CXCR1/2 [196]. Viscolin and bractelactone, which are chalcones from Viscum coloratum and Fissistigma bracteolatum , respectively, also inhibited f MLF-induced O 2 −· production and HNE release by neutrophils; however, these compounds did not inhibit f MLF-induced Ca 2+ flux [198, 199], suggesting targets other than FPR1.…”
Section: Small-molecule Non-peptide Fpr1 Antagonists and Their Synmentioning
confidence: 99%
“…Schepetkin et al (2015) reported that Emethyl cinnamate was not effective in modulating some innate responses like neuthophil migration and ROS production. O. americanum essential oil contained about 55% of methyl cinnamate in its composition; however neither the essential oil extracted from O. americanum nor methyl cinnamate alone were able to induce apoptosis in OCs.…”
Section: Discussionmentioning
confidence: 99%